2020
DOI: 10.3390/s20205769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bout Length on Gait Measures in People with and without Parkinson’s Disease during Daily Life

Abstract: Although the use of wearable technology to characterize gait disorders in daily life is increasing, there is no consensus on which specific gait bout length should be used to characterize gait. Clinical trialists using daily life gait quality as study outcomes need to understand how gait bout length affects the sensitivity and specificity of measures to discriminate pathological gait as well as the reliability of gait measures across gait bout lengths. We investigated whether Parkinson’s disease (PD) affects h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
3
18
2
Order By: Relevance
“…We also observed that circular walking in the lab can moderately represent a patient's everyday gait speed at home (r = 0.61). This association was pronounced in short WBs, which may reflect more complex and demanding gait situations in daily life, such as specific activities including walking and acting with the hands simultaneously [37,43]. Evidence from literature supports this hypothesis: gait features obtained in unsupervised conditions were closer to gait features obtained in the lab during dual-tasking, than when only walking [44][45][46][47].…”
Section: Discussionmentioning
confidence: 71%
“…We also observed that circular walking in the lab can moderately represent a patient's everyday gait speed at home (r = 0.61). This association was pronounced in short WBs, which may reflect more complex and demanding gait situations in daily life, such as specific activities including walking and acting with the hands simultaneously [37,43]. Evidence from literature supports this hypothesis: gait features obtained in unsupervised conditions were closer to gait features obtained in the lab during dual-tasking, than when only walking [44][45][46][47].…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies on the construct validity of turning and gait corroborated that real-world gait and turning performances of PD were impaired (e.g., slower, more variable, and with lower cadence), compared with older adults [ 22–24 ] and reported moderate correlations with clinical scales (e.g., UPDRS) [ 25, 26 ]. Only a few studies have reported criterion validity for digital outcomes, and this was limited to in laboratory or home-like environments [ 25, 27, 28 ].…”
Section: State Of the Art: Where Are We At?mentioning
confidence: 99%
“…Yet, there are additional aspects that need to be considered when real-world gait speed is used as an outcome measure. For example, only a few studies have investigated the gait parameters for different bout durations (e.g., short, medium, long) 30 , 31 . No study has evaluated the metrics derived from the statistical distribution of speed (e.g., mean, median, mode, standard deviation, etc.)…”
Section: Introductionmentioning
confidence: 99%